Hydrothermal synthesis of tellurium nanorods by using recovered tellurium from waste electronic devices. Issue 6 (15th April 2019) - So, Hyeongsub; Yoo, Juyeon; Ryu, Keunhyuk; Yang, MinHo; Lee, Kun-Jae
Abstract: Tellurium (Te) nanostructures with controlled morphology have received the considerable attention in various applications owing to tunable optic, thermoelectric, photoelectronic, piezoelectric, and electrochemical properties. Herein, we introduce the cost-effective and eco-friendly synthesis of Te nanorods (Te NRs) from end of life electronic devices via hydrothermal methods. The Te NRs show the average diameter of 44.6 nm and a length of 358 nm in presence of polyvinylpyrrolidone, as a stabilizing agent. Moreover, the bismuth and intact p-type semiconductor (i.e., Bi0.5 Sb1.5 Te3 ) are selectively recovered as intermediated products. The Te NRs exhibit the NO2 gas sensing properties with concentration as low as 1 ppm at room temperature and fast response/recovery times of 1.59 and 2.10 s at 1 ppm, respectively. We believe that this powerful approach can be expanded to not only selective recovery of valuable materials but synthesis of various nanomaterials from waste electronic devices.